Cellular range extension by optimized two piecewise companding technique for PAPR Reduction with M ary modulation in OFDM system - Amritlal Patel, Himanshu; D. J. Shah, Dr. (International Journal of Engineering and Technology, 2019)
Orthogonal Frequency Division Multiplexing (OFDM) is technique which is used in fifth generation wireless communication era. It is used in Digital Audio Broadcasting, Digital Video Broadcasting, Long Term Evolution etc. One of the drawbacks of OFDM is high Peak to Average Power Ratio (PAPR) in High Power Amplifier (HPA) at the transmitter end. Two Piecewise Companding (TPWC) technique is one of the method to overcome high PAPR problem in OFDM system. It is special technique in which the average power of signal before and after companding transform remains same. Two different functions are used in TPWC in which first function does the expansion of low amplitude signals while second function does the contraction of higher amplitude signals. The optimization parameters are found for Bit Error Rate (BER) of 10-5 considering Eb/No of 19.5 dB with PAPR readings taken at Complementary Cumulative Distributive Function (CCDF) of 10-5.The companding method used gives the lower PAPR. Enhancement of power after PAPR reduction leads to cellular range extension.Â Â